1997
DOI: 10.1111/j.1432-1033.1997.t01-1-00452.x
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of the Enzymatic Characteristics of C4Phosphoenol Pyruvate Carboxylase

Abstract: C, phosphoenolpyruvate (P-pyruvate) carboxylases have evolved from ancestral C, P-pyruvate carboxylases during the evolution of C, photosynthesis (Lepiniec et al., 1994). To meet the requirements of a new metabolic pathway, the C, enzymes have gained distinct kinetic and regulatory properties compared to C, enzymes. Our interest is to deduce the structure responsible for these C,-specific properties. As a model system, the orthologous ppcA P-pyruvate carboxylases of Flaveria trinervia (C,) and Flaveria pringle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
38
0

Year Published

1998
1998
2019
2019

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(43 citation statements)
references
References 54 publications
5
38
0
Order By: Relevance
“…Anity for bicarbonate at pH 8 was in the range 70±110 lM, in agreement with values found in both bacterial and plant PEPCases (Dong et al 1998;Kai et al 1999). Lowering the pH resulted in an increase in S 0.5 PEP value of tomato fruit PEPCase but did not aect V max , which is consistent with previous observations on various C3 and C4 PEPCase isoforms (Chollet et al 1996;Svensson et al 1997;Dong et al 1998). In contrast, tomato fruit PEPCase presented a high I 0.5 malate value at both pH 7.3 (1.1 mM and 0.9 mM for 10-DPA and light-red stages, respectively) and pH 7.1 (0.7 mM and 0.4 mM, respectively).…”
Section: Kinetic Properties Of Tomato Fruit Pepcasesupporting
confidence: 91%
See 1 more Smart Citation
“…Anity for bicarbonate at pH 8 was in the range 70±110 lM, in agreement with values found in both bacterial and plant PEPCases (Dong et al 1998;Kai et al 1999). Lowering the pH resulted in an increase in S 0.5 PEP value of tomato fruit PEPCase but did not aect V max , which is consistent with previous observations on various C3 and C4 PEPCase isoforms (Chollet et al 1996;Svensson et al 1997;Dong et al 1998). In contrast, tomato fruit PEPCase presented a high I 0.5 malate value at both pH 7.3 (1.1 mM and 0.9 mM for 10-DPA and light-red stages, respectively) and pH 7.1 (0.7 mM and 0.4 mM, respectively).…”
Section: Kinetic Properties Of Tomato Fruit Pepcasesupporting
confidence: 91%
“…Among these roles are root nodulation , stomatal opening (Kopka et al 1997), development and germination of seeds (Gonzalez et al 1998;Golombek et al 1999), extension of cotton ®bers (Smart et al 1998) and fruit ripening (Law and Plaxton 1995). Dierent isoforms may exhibit dierent kinetic/regulatory properties, as recently reported for C3 and C4 PEPCase isozymes in Flaveria (Svensson et al 1997). In vivo PEPCase activity is further tightly regulated by positive or negative eectors, phosphorylation state and pH (Chollet et al 1996).…”
Section: Introductionmentioning
confidence: 91%
“…During the evolution of C 4 , the change of a single amino acid residue in the N-terminal region of PEPC, namely from Ala to Ser, was shown to increase the enzyme's kinetic efficiency compared to C 3 sister plants (Svensson et al, 1997;Bläsing et al, 2000;Svensson et al, 2003;Gowik et al, 2006). It was recently shown that in C 4 and CAM species within the Caryophyllales, to which the Talinaceae belong, the isogenes of a recurrently recruited gene lineage encoding PEPC1, namely ppc1-E1c, almost exclusively encodes the C 4 -like Ser-780 (Christin et al, 2014).…”
Section: Facultative Cammentioning
confidence: 99%
“…ppcA orthologous PEPC genes are found in all C 3 and C 3 -C 4 intermediate Flaveria species, indicating that this PEPC gene class was already present in the last common ancestor of present C 3 and C 4 Flaveria species (Westhoff and Gowik, 2004). The comparative enzymatic analysis of ppcA PEPC proteins from C 3 , C 3 -C 4 intermediate, and C 4 Flaveria species revealed that the ppcA PEPCs of F. pringlei (C 3 ) and F. trinervia (C 4 ) are typical C 3 and C 4 PEPCs, respectively, and that only a few amino acid changes, most notably a C 4 invariant Ser residue in the vicinity of the catalytic site, were responsible for the observed differences in kinetic and regulatory behavior (Svensson et al, 1997;Blä sing et al, 2000). The ppcA PEPCs from the C 3 -C 4 species F. pubescens and F. brownii were found to be intermediate, indicating that the ppcA PEPCs changed gradually from C 3 to C 4 (Engelmann et al, 2003), and this PEPC gene class could serve as an evolutionary model to unravel the C 4 -associated changes in enzyme and gene expression characteristics Westhoff and Gowik, 2004).…”
Section: Introductionmentioning
confidence: 99%